Inequality in maternal delays related to maternal death at home and en route to a health facility in Ethiopia: insights from national mortality surveillance data - Neamin Tesfay; Rozina Tariku; Girmay Hailu; Haymanot Firde; Fistum Hadgu Woldeyohannes (BMJ Open)
Objective This study aims to quantify and identify the contributors to inequity in the maternal mortality risk index for deaths occurring at home and en route to health facilities.Design and setting Analysis of the Maternal Death Surveillance and Response data, encompassing maternal deaths reviewed in Ethiopia from 2013 to 2020.Analysis The Maternal Mortality Risk Index was computed using 14 variables grouped according to the three contributors to delay model: contributors to delay in seeking care, contributors to delay in reaching care and contributors to delay in receiving optimal care. Principal component analysis was employed to calculate the index descriptive statistics, and the Erreygers Normalised Concentration Index (ECI) measured inequalities in the maternal mortality risk index across different places of death. Blinder-Oaxaca decomposition analysis identified factors contributing to these disparities in maternal deaths at home and intransit.Participants A total of 4530 reviewed maternal deaths were included in this study.Results ECI was 0.18 (SE 0.02) for maternal deaths occurring at home and 0.12 (SE 0.01) for those en route to a health facility, indicating a higher concentration of deaths among women with a high maternal mortality risk index in both settings. Decomposition analysis identified marital status, educational status, maternal parity and residence as the key contributors to this disparity.Conclusion A notable disparity in the maternal mortality risk index was observed, with home and intransit deaths predominantly affecting women with a high maternal mortality risk index. To reduce these inequalities, efforts should be made to improve community health-seeking behaviour and establish effective referral linkages.